Different Shades of Li4Ti5O12 Composites: The Impact of the Binder on Interface Layer Formation. Issue 10 (17th July 2017) - Nordh, Tim; Jeschull, Fabian; Younesi, Reza; Koçak, Tayfun; Tengstedt, Carl; Edström, Kristina; Brandell, Daniel
Abstract: Replacing the traditional PVdF(‐HFP) electrode binder with water‐soluble alternatives can potentially render electrode fabrication more environmentally benign. Herein, the surface layer formation of stored and cycled samples of two water‐based Li4 Ti5 O12 composites employing either poly(sodium acrylate) (PAA−Na) or sodium carboxymethyl cellulose (CMC−Na) as binders are studied with X‐ray photoelectron spectroscopy. In all three formulations, the surface layer composition formed upon storage differed notably from the solid‐electrolyte interphase (SEI) layer formed on cycled samples. The surface layer under open‐circuit conditions seems to originate mostly from the electrolyte salt (LiPF6 ) degradation. The comparison with cycled samples after 10 and 100 cycles shows a continuous build‐up of an SEI layer on PAA−Na and PVdF‐HFP electrodes. In contrast, on CMC−Na containing electrodes the SEI composition remains nearly unchanged. The results correlate well with the electrochemical behavior. Abstract : A shady affair : Li4 Ti5 O12 composites containing PVdF‐HFP, CMC−Na, or PAA−Na binders are characterized by their electrode morphology and electrochemical performance. The latter is correlated to the composition of the surface layer formation on electrodes either stored for 5 and 10 days or cycled for 10 and 100 cycles.